Glycaemic, gastrointestinal, hormonal and appetitive responses to pearl millet or oats porridge breakfasts: a randomised, crossover trial in healthy humans. Issue 10 (28th November 2019) - Alyami, Jaber; Whitehouse, Ella; Yakubov, Gleb E.; Pritchard, Susan E.; Hoad, Caroline L.; Blackshaw, Elaine; Heissam, Khaled; Cordon, Sally M.; Bligh, H. Frances J.; Spiller, Robin C.; Macdonald, Ian A.; Aithal, Guruprasad P.; et al.
Abstract: Whole-grain cereal breakfast consumption has been associated with beneficial effects on glucose and insulin metabolism as well as satiety. Pearl millet is a popular ancient grain variety that can be grown in hot, dry regions. However, little is known about its health effects. The present study investigated the effect of a pearl millet porridge (PMP) compared with a well-known Scottish oats porridge (SOP) on glycaemic, gastrointestinal, hormonal and appetitive responses. In a randomised, two-way crossover trial, twenty-six healthy participants consumed two isoenergetic/isovolumetric PMP or SOP breakfast meals, served with a drink of water. Blood samples for glucose, insulin, glucagon-like peptide 1, glucose-dependent insulinotropic polypeptide (GIP), peptide YY, gastric volumes and appetite ratings were collected 2 h postprandially, followed by an ad libitum meal and food intake records for the remainder of the day. The incremental AUC (iAUC2h) for blood glucose was not significantly different between the porridges ( P > 0·05). The iAUC2h for gastric volume was larger for PMP compared with SOP ( P = 0·045). The iAUC2h for GIP concentration was significantly lower for PMP compared with SOP ( P = 0·001). Other hormones and appetite responses were similar between meals. In conclusion, the present study reports, for the first time, data on glycaemic and physiological responses to a pearl millet breakfast, showing that this ancient grain could represent a sustainable alternative with health-promoting characteristics comparable with oats. GIP is an incretin hormone linked to TAG absorption in adipose tissue; therefore, the lower GIP response for PMP may be an added health benefit.